Research of Fault Diagnosis Method of Rolling Bearing based on CEEMDAN-DRT - Bie Fengfeng; Gu Sheng; Pang Mingjun; Guo Yue; Yang Gang (Jixie chuandong)
Aiming at the feature extraction for the rolling bearing，a fault diagnosis method based on CEEMDAN adaptive denoising combining with DRT （demodulated resonance technology） is presented.Firstly，the original vibration signal is decomposed into several components with CEEMDAN adaptively，and the reconstruction is performed on regarding the correlation coefficient method to realize the purpose of eliminating noise.Then，the reconstructed signal is analyzed by spectral kurtosisto to achieve the frequency band of the impact component.Based on this，a bandpass filter is designed for the reconstructed signal.Finally，the filtered signals are analyzed by energy Hilbert envelope spectrum.With reference on the characteristic frequency of the rolling bearing failure modes，the pattern of the bearing is recognized.The effectiveness of the method is demonstrated by dynamics simulation and rolling bearing experiments.The result shows that the method can be used to identify the fault information of the rolling bearings effectively.